Gender and rural transformation - Kosec, Katrina; Doss, Cheryl R.; Slavchevska, Vanya (International Food Policy Research Institute, 2020)
Rural transformation is central to the broader structural transformation process taking place in developing countries — fueled by the globalization of value chains, changing food systems, new technologies, conflict and displacement, and climate change, among other factors. Rural transformation refers to the process whereby rural economies diversify into nonfarm activities, agriculture becomes more capital-intensive and commercially oriented, and linkages with neighboring towns and cities grow and deepen (Berdegué, Rosada, and Bebbington 2014). It can bring about fundamental changes in the way businesses and households organize, such as the commercialization and diversification of agricultural production; increased agricultural productivity; migration; and the emergence of a broader set of rural livelihood activities.